English Training Based on Interactive Learning and Character Education at SMAN 1 Nan Sabaris - Yosa Novia Dewi; Khidayatul Munawwaroh; Sri Dewi; Efa Silfia (Fakultas Keguruan dan Ilmu Pendidikan-Universitas Timor, 2025)
This community service program, designed as English training based on interactive learning and character education, aims to enhance both language competence and character development of high school students in preparing for global challenges. The program was conducted over two months through eight online sessions and supported by eight months of intensive mentoring via WhatsApp groups. The training materials integrated Indonesian cultural elements and global issues while instilling the CERMAT character values (Intelligent, Energetic, Brave, Diligent, Millennial, Noble Morals, and Responsible). Evaluation results indicate that the program successfully met participants’ expectations, particularly through interactive learning methods and continuous mentoring that addressed students’ needs. Significant improvements were observed in English skills, including listening, speaking, grammar, writing, and vocabulary, as well as in character aspects such as self-confidence, responsibility, cooperation, and courtesy. With its holistic approach, the program not only strengthened students’ linguistic competence but also fostered positive character development, thereby better preparing them to face challenges at national and global levels. Recommendations for future implementation include greater flexibility in duration and diversification of materials to optimize effectiveness and sustain students’ learning motivation.